Independent and Active Foreign Policy: A New Perspective for Developing National Defense Capabilities - Rizal Yusuf; Amarulla Octavian; Ivan Yulivan; Herlina J.R. Saragih (LPPM Institut Pendidikan Nusantara Global, 2026)
This study explores the strategic transformation of Indonesia’s Bebas Aktif (independent and active) foreign policy as a foundation for strengthening national defense capabilities in the evolving Indo-Pacific security landscape. Historically rooted in non-alignment and moral diplomacy, Bebas Aktif has guided Indonesia’s international engagement since the early post-independence era. However, the twenty-first century’s multipolar order, characterized by technological rivalry, asymmetric threats, and the digitalization of warfare, demands a redefinition of the doctrine into a framework of strategic autonomy. Employing a qualitative–descriptive approach supported by document and thematic analysis, this research examines the convergence of diplomacy, defense modernization, and technological adaptation as instruments of national resilience. The findings reveal that Indonesia’s evolving policy behavior increasingly reflects instrumental neutrality, in which defense diplomacy and multilateral cooperation enhance sovereignty without dependency. Furthermore, the adoption of Network-Centric Warfare (NCW), cyber diplomacy, and defense-industrial partnerships illustrates Indonesia’s transition from moral leadership to strategic maturity. Nonetheless, challenges persist in interagency coordination, cyber vulnerability, and industrial capacity. The study concludes that integrating diplomacy and defense within a comprehensive national strategy anchored by technological innovation and human capital development is imperative for Indonesia to maintain sovereignty and influence amid global power competition. Thus, Bebas Aktif emerges not as a relic of neutrality but as a dynamic doctrine of adaptive resilience in the Indo-Pacific era.